Humanitarian intervention in the context of the crime of aggression under article 8bis of the Rome Statute - Radmanović, Jelena S (Glasnik Advokatske komore Vojvodine, 2021)
Although it does not constitute a new concept in international law, humanitarian intervention provokes a lot of controversy when it comes to its constituent elements and its applicability. As this is a legal institute most closely related to the situations of use of force in international relations, the institute of humanitarian intervention finds its potential application in the sphere of international criminal law as well, particularly with regard to the crime of aggression under Article 8bis of the Rome Statute, which criminalizes the use of force outside the framework set by the Charter of the United Nations. The paper attempts to answer the question of whether humanitarian intervention, if accepted as an international customary rule, can and in which way affect the application of the provisions of the Rome Statute. In addition to the analysis of the significance of humanitarian intervention when it comes to determining on the fulfillment of the elements of the crime of aggression, the paper will attempt to indicate the reach that this institute may have when it comes to the exclusion of criminal responsibility under the Rome Statute, pointing out the possible defense strategies in potential proceedings before the International Criminal Court.